Effects of auricular acupoint acupuncture therapy on postoperative pain in patients undergoing surgery for low anal fistula (耳穴揿针疗法改善低位单纯性肛瘘术后疼痛的效果观察及机制研究) - YANG Jin (杨瑾); XIE Wei (谢薇); XIAO Cheng (肖成); ZHANG Fang (张芳); HU Ying (胡莹) (Journal of International Translational Medicine Limited, 2022)
Objective To investigate the effect of auricular acupoint acupuncture therapy on postoperative pain in patients undergoing surgery for low anal fistula. Methods Totally 60 patients undergoing surgical treatment for low anal fistula were divided into the control group (n=30) and acupuncture group (n=30) by using the random number table method. In the control group, on the basis of conventional treatment, 20 mg of paracetamol and dihydrocodeine tartrate was taken orally 30 min before dressing change and going to bed in the evening every day. In the acupuncture group, after the patient returned to the ward after surgery, the acupuncture was applied to the four auricular acupoints of Zhichang, Gangmen, Jiaogan and Shenmen at 8 am every morning. The VAS scores of the two groups were observed after changing the dressing every day for five days after the operation, and the changes of β-EP and CRP concentration in the venous blood before and 5 days after the treatment were observed. Results VAS scores of patients in the acupuncture group were lower than those in the control group five days after surgery, and the difference was statistically significant (P＜0. 05). Compared with the control group, there was no significant difference in the levels of β-EP and CRP before treatment(P＞0. 05), and there was significant difference after 5 days of treatment(P＜0. 05). Conclusion Auricular acupoint acupuncture therapy can alleviate postoperative pain, promote the release of β-EP, inhibit the secretion of CRP, reduce inflammation, and improve the therapeutic effect of surgical treatment for low anal fistula. (目的 探讨耳穴揿针治疗对低位单纯性肛瘘患者术后疼痛的影响。方法 选取医院肛肠科2021年1月-6月收治的低位单纯性肛瘘术后患者60例, 采用随机数字表法将患者分为对照组(n=30)与揿针组(n=30)。对照组在常规治疗基础上, 于每日换药前30 min及晚上睡前口服氨酚双氢可待因20 mg; 揿针组在患者术毕安全返回病房后、术后每天上午8时使用揿针贴于耳穴直肠、肛门、交感、神门四穴。观察两组患者术后5 d内每天换药后疼痛评分情况, 以及治疗前、治疗5 d后静脉血血浆中β-内啡肽(β-EP)含量和C反应蛋白(CRP)浓度变化。结果 揿针组患者术后5 d换药后VAS评分均低于对照组, 差异有统计学意义(P＜0. 05)。揿针组与对照组相比, β-EP、CRP水平治疗前差异无统计学意义(P＞0. 05), 治疗5 d后差异有统计学意义(P＜0. 05)。结论 耳穴揿针治疗运用于肛瘘术后患者, 可以减轻患者疼痛感, 并促进β-EP的释放, 抑制CRP的分泌, 减轻炎症反应, 提高治疗效果。)